Messaritis, Vassilios - (:unkn) unknown (My University, 2026)
Vassilios Messaritis is an Assistant Professor (Entagmenos) in the Department of Mechanical Engineering and Materials Science and Engineering. After graduating the Cyprus Higher Technical Institute in Mechanical Engineering he continued his studies at Dundee University, Scotland U.K. where he received a BSc (Hon) in Mechanical Engineering. At Dundee University he also received his PhD on the theme of “Investigation of Acoustic Emission Signal Characteristics in Monitoring Cutting Tool Wear.” He worked in Cyprus with a Building Services Consulting office and also with a Manufacturing Assembling Firm as an Assistant to the Technical Director responsible for the improvement of production and productivity of the activities of the firm. For a significant number of years he worked as a Lecturer in Production Engineering with the Cyprus Higher Technical Institute in the Department of Mechanical and Marine Engineering. He was mainly lecturing subjects such as Production Engineering, Metrology and Quality Control and Production/Operations Management. His research interests are Condition Monitoring by the method of Acoustic Emission of the machining operation for the improvement of quality and productivity of automatic machine tools and in the use of Acoustic Emission in other applications such as monitoring in real time, initiation of cracks, fatigue failure in structures and pressure vessels as well as the delamination of composite materials.